2014
DOI: 10.1111/hel.12132
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Epithelium with Low‐Grade Atypia Appears on the Surface of Gastric Cancer after Successful Helicobacter pylori Eradication Therapy

Abstract: Epithelium with low-grade atypia on gastric cancer tissue, which may develop from gastric cancer cells, is frequently present after successful eradication therapy. This phenomenon could influence the practice of endoscopic diagnosis of gastric cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 21 publications
6
55
0
Order By: Relevance
“…In our study, several cases in the GCE group also indicated low atypia resembling non-neoplastic epithelium in surface GC cells; moreover, the Ki-67 index was reduced in this area. This finding supports the decrease in inflammation observed in GC following eradication [16, 22, 46]. It is unclear whether these epithelial cells with low atypia were derived from tumor cells or not.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In our study, several cases in the GCE group also indicated low atypia resembling non-neoplastic epithelium in surface GC cells; moreover, the Ki-67 index was reduced in this area. This finding supports the decrease in inflammation observed in GC following eradication [16, 22, 46]. It is unclear whether these epithelial cells with low atypia were derived from tumor cells or not.…”
Section: Discussionsupporting
confidence: 84%
“…It is unclear whether these epithelial cells with low atypia were derived from tumor cells or not. Kitamura et al [16] described that the origin of these cells was not unclear; however, they indicated the possibility that low atypical epithelium may develop from GC cells by the influence of H. pylori eradication.…”
Section: Discussionmentioning
confidence: 99%
“…As well as histological surface differentiation of cancer [13], surface epithelium with low-grade atypia has also been reported [14]. All of these histological findings were reported to make endoscopic diagnosis difficult, although it remains unresolved whether the latter two types of epithelium are neoplasia or non-neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…2c). In all tumor sections, NE was marked, and its coverage rate on the cancer surface was determined and classified into 4 grades in accordance with a previous study [21]: grade 0, 0% of the tumor length; grade 1, < 5% of the tumor length; grade 2, < 30% of the tumor length; and grade 3, ≥30% of the tumor length. Moreover, the presence or absence of NE at the tumor border, which was assumed to affect the assessment of the DL, was also assessed separately.…”
Section: Methodsmentioning
confidence: 99%